Commonalities in alpha and beta neural desynchronizations during prediction in language comprehension and production. (December 2020) - Gastaldon, Simone; Arcara, Giorgio; Navarrete, Eduardo; Peressotti, Francesca
Abstract: The present study investigates whether predictions during language comprehension are generated by engaging the language production system. Previous studies investigating either prediction or production highlighted M/EEG desynchronization (power decrease) in the alpha (8–10 Hz) and beta (13–30 Hz) frequency bands preceding the target. However, it is unclear whether this electrophysiological modulation underlies common mechanisms. We recorded EEG from participants performing both a comprehension and a production task in two separate blocks. Participants listened to high and low constraint incomplete sentences and were asked either to name a picture to complete them (production) or to simply listen to the final word (comprehension). We found that in a silent gap before the final stimulus, predictable stimuli elicited alpha and beta desynchronization in both tasks, signaling the pre-activation of linguistic information. Source estimation highlighted the involvement of left-lateralized language areas and temporo-parietal areas in the right hemisphere. Furthermore, correlations between the desynchronizations in comprehension and production showed spatiotemporal commonalities in language-relevant areas of the left hemisphere. As proposed by prediction-by-production models, our results suggest that comprehenders engage the production system while predicting upcoming words.